Connectivity properties for subspaces of function spaces determined by fixed points - Daciberg L. Gonçalves; Michael R. Kelly (Abstract and Applied Analysis)
We study the topology of a subspace of the function space of continuous self-mappings of a given manifold: the subspace determined by maps having the least number of fixed points in its homotopy class. In the case that the manifold is a closed disk of finite dimension, we prove that this subspace is both globally and locally path connected. We also prove this result when the manifold is a sphere of dimension 1, 3, or 7.